94=-2(1-6m)

Simple and best practice solution for 94=-2(1-6m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 94=-2(1-6m) equation:


Simplifying
94 = -2(1 + -6m)
94 = (1 * -2 + -6m * -2)
94 = (-2 + 12m)

Solving
94 = -2 + 12m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-12m' to each side of the equation.
94 + -12m = -2 + 12m + -12m

Combine like terms: 12m + -12m = 0
94 + -12m = -2 + 0
94 + -12m = -2

Add '-94' to each side of the equation.
94 + -94 + -12m = -2 + -94

Combine like terms: 94 + -94 = 0
0 + -12m = -2 + -94
-12m = -2 + -94

Combine like terms: -2 + -94 = -96
-12m = -96

Divide each side by '-12'.
m = 8

Simplifying
m = 8

See similar equations:

| N^2=3n+4 | | 4x-5=(3x-10) | | 25x^2-15x-54=0 | | 2x^3+3x-12=0 | | 4-l(l-2x)=-l*2x | | 4x+2y=45 | | 2. 3p+14=41 | | 2(r+6)-3(r-6)=60 | | 3n-10=54 | | 4sinx-7=1 | | 5x-3x/4=50 | | -24=a+[-27] | | 6-2.2= | | y-(-9)=6/7x(x-(-2)) | | m-(-2)=12 | | -(X-7)=2 | | x^3+3xy^2=1 | | 5891/76= | | 9y+8+5y-2=90 | | 5(5)+4(2x-8)=33 | | 30/50=80 | | c=2(3.14)(10) | | 5x+4(2x-8)=33 | | 3x-10=-8x+6 | | x+19=5x+7 | | 12x^2+2x^4=14 | | (×/6)-6=4 | | 99=x+(x-1) | | 5-3n=3.5n-8 | | 7x-2x+1=3x+11 | | 4x+11x-69=0 | | x^2-8x+y^2-32y=263 |

Equations solver categories